The war pianist - Robotham, Mandy (Avon, 2023)
"Blitz-ridden London: Marnie Fern's life is torn apart when her grandfather is killed in an air raid. But once she discovers that he'd been working undercover as a radio operative - or pianist - for the Dutch resistance, Marnie knows she must complete his mission - no matter the cost. Nazi-occupied Amsterdam: At the other end of the wireless, fellow pianist Corrie Bakker is caught in a dangerous game of cat-and-mouse as she desperately tries to keep her loved ones out of the line of fire - even if it means sacrificing herself. Bound together by the invisible wires of their radios, the two women lead parallel lives in their home cities, as both are betrayed by those they trust the most. But when the Nazis close in on one of them, only the other can save her."--